2011
DOI: 10.1177/0145721710397385
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Educators in Safety-Net Practices

Abstract: This study underscores the need for diabetes educators and other health education professionals to be creative and flexible in delivering self-management education to patients in underserved settings. The complexity of diabetes care and the self-care responsibilities placed on the patient reinforce the need for a team approach such as that proposed in the medical home model and should include certified diabetes educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…With the onset of patient-centered medical homes, newer models of training and embedding diabetes educators are available, and may offer opportunity for delivering self-management support to patients. 32,33 This study has several limitations. Clinics and not patients were randomized and baseline differences were noted between arms that were accounted for in statistical analyses.…”
Section: Discussionmentioning
confidence: 94%
“…With the onset of patient-centered medical homes, newer models of training and embedding diabetes educators are available, and may offer opportunity for delivering self-management support to patients. 32,33 This study has several limitations. Clinics and not patients were randomized and baseline differences were noted between arms that were accounted for in statistical analyses.…”
Section: Discussionmentioning
confidence: 94%
“…Similar barriers to GE completion have been described by other educators, especially those in underserved settings. 23,24 But even b Hemoglobin A 1c tests were performed at 1 of 2 accredited laboratories using standard high-pressure liquid chromatography assay methods with a CV of 1.14% at an HbA 1c level of 7.5% (HPMG) and a CV of 0.82% at an HbA 1c level of 6.2% (LCF Research/ABQ HP). Hemoglobin A 1c values were log transformed in the analysis and then retransformed back to their original scale (presented as geometric means).…”
Section: Commentmentioning
confidence: 99%
“…16 However, for those who are underserved, many do not benefit from DSME 17 due to existing barriers such as language and literacy, health beliefs and cultural considerations, competing obligations, and poor access. [18][19][20][21][22] To address these barriers, the National Institutes of Health created a Clear Communication initiative to establish plain-language approaches to incorporating both cultural respect and new technologies to overcome issues related to low health literacy. 23 Research has identified that low health literacy undermines the comprehension and self-efficacy needed for health self-management.…”
mentioning
confidence: 99%